2022
DOI: 10.1093/nar/gkac055
|View full text |Cite
|
Sign up to set email alerts
|

RBFOX2 is required for establishing RNA regulatory networks essential for heart development

Abstract: Human genetic studies identified a strong association between loss of function mutations in RBFOX2 and hypoplastic left heart syndrome (HLHS). There are currently no Rbfox2 mouse models that recapitulate HLHS. Therefore, it is still unknown how RBFOX2 as an RNA binding protein contributes to heart development. To address this, we conditionally deleted Rbfox2 in embryonic mouse hearts and found profound defects in cardiac chamber and yolk sac vasculature formation. Importantly, our Rbfox2 conditional knockout m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 70 publications
2
28
0
Order By: Relevance
“…Consistent with this finding, a previous report documented decreased expression of sarcomere and mitochondrial components in Rbfox2-depleted rat myoblasts due to alternative polyadenylation 33 . However, conditional knock-out of Rbfox2 in the embryonic mouse heart was linked to changes in alternative splicing of transcripts involved in cell adhesion to the extra-cellular matrix 14 , a process not readily identified in our datasets. Therefore, a more comprehensive cross-species comparison of alternative splicing changes caused by loss of Rbfox2 in the heart could be informative.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Consistent with this finding, a previous report documented decreased expression of sarcomere and mitochondrial components in Rbfox2-depleted rat myoblasts due to alternative polyadenylation 33 . However, conditional knock-out of Rbfox2 in the embryonic mouse heart was linked to changes in alternative splicing of transcripts involved in cell adhesion to the extra-cellular matrix 14 , a process not readily identified in our datasets. Therefore, a more comprehensive cross-species comparison of alternative splicing changes caused by loss of Rbfox2 in the heart could be informative.…”
Section: Discussionmentioning
confidence: 85%
“…Arguing against pathogenicity, mice with Rbfox2 deleted in Mlc2v + cardiomyocytes are born with grossly normal hearts 13 . However, a recent report demonstrated that earlier deletion of Rbfox2 in Nkx2.5 + cells, which include cardiac progenitors, is embryonic lethal by E11.5 14 . Specifically, these animals are severely growth impeded and display gross morphological defects in cardiac chamber, common outflow tract, and yolk sac vasculature development.…”
Section: Introductionmentioning
confidence: 99%
“…We identified the upregulation of two transcription regulators, RBFOX2 and FOXD1 , in high-risk UM. RBFOX2 is known to be involved in cerebellar and heart development [ 49 , 50 ], and FOXD1 is involved in retina development [ 51 , 52 ], but to our knowledge neither have been associated with melanocyte development prior to this study. RBFOX2 is a well-known regulator of epithelial-to-mesenchymal transition [ 53 ], where the alternate splicing of pre-mRNA alters signal transduction via a wide range of genes depending on cellular context [ 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that CELF1 is up-regulating in the hearts of T1DM mice, but diabetes-induced AS alterations are consistent with CELF1 depletion or decreased CELF1 splicing activity ( Blech-Hermoni et al, 2016 ; Belanger et al, 2018 ). Interestingly, RBFox2, an RNA-binding protein belonging to the RBFOX family, that is involved in AS regulation in heart diseases, shows the same trend as CELF1 ( Gazzara et al, 2017 ; Verma et al, 2022 ). RBFox2 regulates cardiac function-related genes associated with diabetic cardiomyopathy.…”
Section: Rbps and Diabetic Complicationsmentioning
confidence: 97%
“…RBPs can regulate pre-mRNA alternative splicing (AS) through binding to the pre-mRNA and interacting with the spliceosome components, which generate variant protein isoforms from a single gene, resulting in transcriptome and proteome diversity ( Sperling, 2017 ). Previous studies demonstrated that AS controlled by RBPs plays a crucial role in diabetes and its complications ( Verma et al, 2013 ; Nutter et al, 2016 ; Gazzara et al, 2017 ; Belanger et al, 2019 ; Verma et al, 2022 ). The role of RBPs in AS will be discussed in detail in the next section.…”
Section: Roles Of Rna-binding Proteinsmentioning
confidence: 99%